Exploring Student Perspectives on Restorative Justice: A Case Study at the Public High School of Kefamenanu - Manubulu, Isakh Benyamin; Tahu, Maria Filiana; Astariyani, Ni Luh Gede; Da Cruz, Rosino; Tuasikal, Ditha Fomora (Universitas Negeri Semarang, 2024)
The exploration of Restorative Justice (RJ) in Indonesia's border areas, particularly within the context of North Central Timor High School, reveals intriguing insights into its implementation and reception among students. This study, employing an empirical legal research approach focused on statutory analysis, factual examination, and thoughtful analysis, sheds light on the evolving landscape of Indonesia's criminal justice system. Notably, the research highlights that while PERMENDIKBUD 46/23 initially adopts a distributive punishment framework, there exists a growing inclination towards adopting RJ principles. A significant proportion of students, constituting 55.50%, express strong support for the incorporation of RJ within the school environment. Moreover, a majority (51%) acknowledge the presence of RJ initiatives within their schools, emphasizing the gradual acceptance of this alternative approach. Furthermore, the findings underscore the importance of transparency in RJ practices, with 40% of students recognizing its significance. Additionally, a notable percentage (35.5%) of students endorse the application of RJ in addressing issues of sexual violence, signaling a potential avenue for addressing such sensitive matters within the school community. Crucially, a substantial proportion (43.33%) of students advocate for the active involvement of schools in facilitating the resolution of sexual violence cases through RJ processes. This underscores the pivotal role educational institutions can play in fostering a culture of accountability and restoration. Overall, the student perspectives elucidated in this research offer valuable insights into the feasibility and efficacy of RJ in addressing not only disciplinary matters but also complex issues like sexual violence within educational settings. As Indonesia continues to explore innovative approaches to justice, the embrace of RJ principles signifies a promising step towards fostering a more inclusive and restorative justice system.